Students’ Anxiety in Learning German: Types, Levels, Effects and Strategies - Susianti, Hartanti Woro (LACULTOUR: Journal of Language and Cultural Tourism, 2024)
Foreign language anxiety is a psychological factor that significantly influences the process of acquiring a foreign language. This anxiety often manifests as feelings of incompetence triggered by concerns about being monitored, judged, or compared to others. This study on the anxiety experienced by students learning German at Bali Tourism Polytechnic (BiTP) employs a qualitative approach using case study and phenomenological methods. Data were collected through in-depth interviews, participatory classroom observations, and related documents. The data were analyzed using thematic analysis methods. The research findings indicate that students experience various types of anxiety, such as state anxiety, situation-specific anxiety, anxiety in testing situations, facilitating anxiety, and debilitating anxiety. The levels of anxiety experienced by the students were mostly low to moderate. Foreign language anxiety has negative impacts, such as decreased performance, avoidance of language-use situations, and reduced motivation. However, anxiety can also have positive effects when managed well, such as serving as motivation to study harder. To minimize anxiety, instructors can provide positive feedback, prepare adequate materials and exercises, use collaborative and supportive teaching methods, and encourage students to focus on the learning process and their personal development.